La superación del paradigma territorial y sus efectos en el Derecho Administrativo. Bases normativas del Derecho Administrativo transnacional - Agudo González, Jorge (Revista de Derecho Político, 2018)
Resumen: El Derecho Administrativo aborda con creciente frecuencia fenómenos jurídicos que podemos denominar como «transnacionales». Esta calificación se debe a que no son susceptibles de una ordenación integral por el Derecho Administrativo estatal. En este estudio abordamos el análisis de esos fenómenos jurídicos desde la perspectiva del principio de territorialidad. El objetivo es mostrar los efectos de la incompatibilidad de fenómenos inherentes a la globalización con el paradigma de la territorialidad del Derecho Administrativo y su concepción estatutaria como Derecho del Estado. El estudio comienza con una exposición sobre la trascendencia del principio de territorialidad en la Teoría General del Estado y en la Teoría jurídica; esta parte analiza la relevancia del territorio como base y límite del poder público, y en las relaciones con otros ordenamientos. A continuación, el estudio aborda los fenómenos jurídicos alumbrados en el contexto actual de fragmentación y pluralismo jurídico, para mostrar una realidad jurídica que condiciona la capacidad explicativa del principio de territorialidad. La constatación de la superación del paradigma territorial del Derecho Administrativo provoca la necesidad de afrontar las consecuencias de ese panorama jurídico transformador. El estudio muestra cómo la desterritorialización del Derecho tiene implicaciones directas no sólo en las relaciones entre órdenes normativos, sino también en la summa divisio, al igual que en la vis autoritaria que tradicionalmente ha caracterizado al Derecho Administrativo. Estas transformaciones abren paso a un Derecho Administrativo no exclusivamente estatal, basado en relaciones interordinamentales y focalizado en relaciones jurídicas dinámicas. Summary I. Introduction. II. The Territoriality Principle in the State General Theory and in the Legal Theory. 1. The territoriality and exclusivity principles of sovereign power. 2. State law «toward outward». 2.1. Foundations of international law. 2.2. Conflicts of laws and private international Law. III. The Loss of Centrality of the Territoriality Principle. 1. The overcoming of the exclusivity of State law. 1.1. Legal fragmentation and international (private) «norms». 1.2. Administrative law is international law and vice versa. 1.3. Relations between State legal orders. 2. The overcoming of the division public law versus private law. IV. Final Remarks: the «Relational Character» of the Transnational Administrative Law. 1. From the exclusivity and the completness of the State Administrative Law to the relations between legal orders and conflicts of law. 2. From an authoritarian conception centered in static legal status, to a conception ex parte civium and focused on dynamic legal relationships. Abstract: Administrative Law is increasingly tackling with legal phenomena that can be named as «transnational». This denomination is due to the fact that cannot be embraced entirely by State Administrative Law. In this paper we approach the analysis of these legal phenomena from the perspective of the territoriality principle. The objective of this paper is to show the effects of the incompatibility of a legal phenomenon inherent to globalization, with the paradigm of the territoriality of Administrative Law and its statutory conception as State law. The study begins with an exposition on the relevance of the territoriality principle in the State General Theory and in the Legal Theory; for this reason, we analyze the relevance of the territory as the basis and limit of public power, but also in the relations other legal orders. Then the study deals with the current context of fragmentation and legal pluralism to show a legal reality that undermines the explanatory capacity of the territoriality principle. The verification of the overcoming of the territorial paradigm of Administrative Law causes the need to face the consequences of this transforming legal reality. The paper shows to what extent the deterritorialization of law has direct implications not only in the relations between legal orders, but also in the «summa divisio» and in the traditional authoritarian characterization of Administrative Law. These changes open the scene to a non-statist legal regime, based on relations between legal orders and focused on dynamic legal relations.